2013
DOI: 10.1038/srep01843
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic sequencing reveals microbiota and its functional potential associated with periodontal disease

Abstract: Although attempts have been made to reveal the relationships between bacteria and human health, little is known about the species and function of the microbial community associated with oral diseases. In this study, we report the sequencing of 16 metagenomic samples collected from dental swabs and plaques representing four periodontal states. Insights into the microbial community structure and the metabolic variation associated with periodontal health and disease were obtained. We observed a strong correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
202
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(214 citation statements)
references
References 42 publications
10
202
0
2
Order By: Relevance
“…Notably, functions related to bacterial motility, energy metabolism, lipopolysaccharide (LPS) biosynthesis, flagellar assembly, methane metabolism, bacterial chemotaxis, and peptidases were abundant in chronic periodontitis cases. These results are consistent with recent metagenomic data (34,53). Going forward, elucidating the role of key bacteria encoding these functions and understanding the basis of individual variations in microbiomes and metagenomes will be essential in future studies.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Notably, functions related to bacterial motility, energy metabolism, lipopolysaccharide (LPS) biosynthesis, flagellar assembly, methane metabolism, bacterial chemotaxis, and peptidases were abundant in chronic periodontitis cases. These results are consistent with recent metagenomic data (34,53). Going forward, elucidating the role of key bacteria encoding these functions and understanding the basis of individual variations in microbiomes and metagenomes will be essential in future studies.…”
Section: Discussionsupporting
confidence: 87%
“…Several groups have since used the 16S rRNA and metagenomic approaches to survey subgingival microbiota from subjects recruited in the community (30,33). These "community" data sets have demonstrated a difference between periodontitis-associated and health-associated microbiota in both the overall microbial community structure (30,31) and the predicted functional capabilities (34,35). A number of bacterial taxa and genes were found to be differentially abundant between health and disease.…”
mentioning
confidence: 99%
“…The taxonomic shift of microbiota was accompanied by a functional shift: the observed gingivitis-enriched functions such as flagellar biosynthesis might be traced to bacterial oral mobility, as the flagellar can assist invading host tissues and escaping phagocytosis (Siqueira and Rocas, 2007). For example, Treponema, Selenomonas and Campylobacter, which were among the gingivitis biomarkers in our MiG model, were among the major donors of flagellar biosynthesis pathways in the plaque microbiota of periodontal disease (Wang et al, 2013); in fact, many species in these genera are equipped with flagella (Ruby et al, 1997;Ihara et al, 2003;Liu et al, 2010;Haya et al, 2011). Our study also unraveled a microbial basis for the heterogeneity of disease outcome in human population.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, several potential markers of type-II hosts (for example, Selenomonas, Peptostreptococcus, unclassified Lachnospiraceae, unclassified Veillonellaceae and Oribacterium), who exhibited higher disease acuteness and susceptibility to recurrence, were also found to be enriched in periodontitis (Griffen et al, 2012). Furthermore, a recent study reported a functional link in oral microbiota between gingivitis and periodonititis patients (Wang et al, 2013).Therefore, the collective evidence supported a link between severe gingivitis and periodontitis, and also provided a possible explanation of the variation of periodontitis susceptibility in human populations.…”
Section: Discussionmentioning
confidence: 96%
“…Both of culture-dependent and -independent methods have been used in order to illustrate microbial biodiversity in human dental plaques that cause periodontal disease (17)(18)(19)(20)(21). The most abundant microbial species in dental plaques annotated to periodontal disease signature pathogens are the Gram-negative Porphyromonas gingivalis, Tannerella denticola and T. forsythia (22).…”
Section: Introductionmentioning
confidence: 99%